Lalalalovesongs [compact disc] - Mraz, Jason (Atlantic Catalog Group, 2022)
The greatest love songs from Jason Mraz in one collection, featuring "I'm Yours," "I Won't Give Up," "Lucky, " "Love Someone," and many more timeless hits and fan favorites.